2019
DOI: 10.1016/j.ifset.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Resistance changes in Salmonella enterica serovar Typhimurium treated by High Hydrostatic Pressure and Pulsed Electric Fields and assessment of virulence changes by using Caenorhabditis elegans as a test organism

Abstract: Resistance changes in Salmonella enterica serovar Typhimurium treated by high hydrostatic pressure and pulsed electric fields and assessment of virulence changes by using Caenorhabditis elegans as a test organism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Additional studies are also demonstrated the development of resistance when S. enterica var Typhimurium is treated with non-essential oil natural antimicrobials (polyphenols) (Gupta and Birdi, 2017). Under other sub-lethal physical treatments, like Pulsed Electric Fields and High Hydrostatic Pressure, S. enterica var Typhimurium has also demonstrated ability to be adapted (Sanz-Puig et al, 2018) In order to further understand the mechanism of resistant bacteria infection, and the possible evident changes in virulence due to this adaptation step in relation to untreated bacteria, the C. elegans in vivo model was used. Up to date, over human pathogens have been analyzed in the C. elegans infection model (Battisti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies are also demonstrated the development of resistance when S. enterica var Typhimurium is treated with non-essential oil natural antimicrobials (polyphenols) (Gupta and Birdi, 2017). Under other sub-lethal physical treatments, like Pulsed Electric Fields and High Hydrostatic Pressure, S. enterica var Typhimurium has also demonstrated ability to be adapted (Sanz-Puig et al, 2018) In order to further understand the mechanism of resistant bacteria infection, and the possible evident changes in virulence due to this adaptation step in relation to untreated bacteria, the C. elegans in vivo model was used. Up to date, over human pathogens have been analyzed in the C. elegans infection model (Battisti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are also demonstrated the development of resistance when S. enterica var Typhimurium is treated with non-essential oil natural antimicrobials (polyphenols) (Gupta and Birdi, 2017). Under other sub-lethal physical treatments, like Pulsed Electric Fields and High Hydrostatic Pressure, S. enterica var Typhimurium has also demonstrated ability to be adapted (Sanz-Puig et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium) were provided by the Spanish Type Culture Collection. Following the procedure described by Sanz-Puig et al [ 35 ], lyophilized samples (0.5 g lyophil) were rehydrated in Tryptone Soy Broth (TSB) (Scharlab S.A., Barcelona, Spain) ( L . monocytogenes and S .…”
Section: Methodsmentioning
confidence: 99%
“…Pure cultures of Listeria monocytogenes serovar 4b (Spanish Type Culture Collection (CECT) 4032) (L. monocytogenes), Escherichia coli O157:H7 (CECT 5947) (E. coli) and Salmonella enterica serovar Typhimurium (CECT 443) (S. Typhimurium) were provided by the Spanish Type Culture Collection. Following the procedure described by Sanz-Puig et al [35], lyophilized samples (0.5 g lyophil) were rehydrated in Tryptone Soy Broth (TSB) (Scharlab S.A., Barcelona, Spain) (L. monocytogenes and S. Typhimurium) or in Luria Broth (LB) (Scharlab S.A., Barcelona, Spain) (E. coli). Rehydrated cultures were transferred to 500 mL of its corresponding media and incubated in a bath shaker (200 rpm) for 14 h at 37˚C.…”
Section: Microbial Strainsmentioning
confidence: 99%
“…Salmonella enterica serovar Typhimurium and Cronobacter sakazakii are foodborne pathogens that are highly relevant to the food processing industry (Endersen et al, 2017;Sanz-Puig et al, 2018). In 2016, 300,524 cases of foodborne outbreaks were reported in Europe, of which 26.22% were caused by Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%